The contribution of nitrogen by promiscuous soybeans to maize based cropping the moist savanna of Nigeria - Sanginga, N.; Okogun, J.; Vanlauwe, Bernard; Dashiell, Kenton E. (Springer, 2002)
Agronomic results indicate that maize grain yields generally are higher when the crop is planted following soybean than in continuous maize cultivation in the moist savanna agroecological zones of West Africa. Many factors have been hypothesized to explain this phenomenon, including enhanced N availability and the so-called `rotational effect'. There is, however, hardly any quantitative information on the residual N benefits of promiscuous soybeans to subsequent cereal crops grown in rotation with soybean. Three IITA promiscuous soybean breeding lines and two Brazilian soybean lines were grown in 1994 and 1995 at Mokwa in the southern Guinea savanna, Nigeria, to quantify the nitrogen contribution by soybeans to a succeeding crop of maize grown in rotation with soybean for two consecutive years, 1996 and 1997 using two methods of introducing 15N into soil (fresh 15N labelling and its residual 15N) and three maize cultivars (including one cultivar with high N use efficiency) used as reference plants. The nodulating soybeans fixed between 44 and 103 kg N ha−1 of their total N and had an estimated net N balance input from fixation following grain harvest ranging from −8 to 43 kg N ha−1. Results in 1996 and in 1997 showed that maize growing after soybean had significantly higher grain yield (1.2 – 2.3-fold increase compared to maize control) except for maize cultivar Oba super 2 (8644-27) (a N-efficient hybrid). The 15N isotope dilution method was able to estimate N contribution by promiscuous soybeans to maize only in the first succeeding maize crop grown in 1996 but not in the second maize crop in 1997. The first crop of maize grown after soybean accumulated an average between 10 and 22 kg N ha−1 from soybean residue, representing 17–33% of the soybean total N ha−1. The percentage 15N derived from residue recovery in maize grown after maize was influenced by the maize cultivars. Maize crop grown after the N-efficient hybrid cultivar Oba Super 2 (844-27) had similar 15N values similar to maize grown after soybeans, confirming the ability of this cultivar to use N efficiently in low N soil due to an efficient N translocation ability. The maize crop in 1997 grown after maize had lower 15N enrichment than that grown in soybean plots, suggesting that soybean residues contributed a little to soil available N and to crop N uptake by the second maize crop. The differential mineralization and immobilization turnover of maize and soybean residues in these soils may be important and N contribution estimates in longer term rotation involving legumes and cereals may be difficult to quantify using the 15N labelling approaches. Therefore alternative methods are required to measure N release from organic residues in these cropping systems.